PATI KA TiI SEPA " RITUS KORBAN MASYARAKAT ADAT ENDE-LIO DIKABUPATEN ENDE - Kosmas Minggu (Media Bina Ilmiah, 2023)
At first, Pati Ka Tii Sepa was a sacrificial rite for atonement for sins so that humans would avoid punishment/curse or calamity, but then with the development of the times more advanced so that in every ritual ceremony the Ende-Lio indigenous people in general and "Frozen Ngeo Mosa Ngeo" ' in particular always brings sacrifices, so the notion of ''Pati Ka Tii Sepa'' changes and then becomes broader in terms of all kinds of sacrifices and ceremonies to avoid curses, calamities, disasters and also as an expression of gratitude and gratitude for success in a business. Pati Ka Tii Sepa'' is all matter. This does not mean that Pati Ka Tii sepa is a manipulative act to get revenge from the Supreme, considering that the giving of material goods is only an expression of the sincerity of the human heart, the actions of victims and prayers of supplication. Sacrificial materials are always the best of human works or all objects that are highly valued in society. This shows how high the values ​​of kindness they uphold. Kindness is actually a state of safety. And the safety situation is not thought of as an abstract situation but very concrete. Concrete salvation concerns the state of being free from all everyday suffering or situations characterized by intimacy with one another. If it is said that real safety, a secure, peaceful, established state can only be maintained by complying with all the patterns of life that have been passed down by the ancestors from generation to generation. Through ritual sacrifices, a situation of salvation that has been lost or even extinct can be regained. According to the Beku Ngeo Mosa Ngeo indigenous people, salvation is so real that the idea of ​​salvation in any religion may complement the existing view. To him was given all other creations and the power to manage what is on earth. Dealing with Dua Lulu Wula Nggae Longgo Leja and Ata Mata Wena Tana, meaning (God above the moon, God above the sun and the dead or the Ancestors under the land of humans are still limited). Thus man finds himself in Dua Nggae as being, which is limited at the same time who has optimism because of his total dependence on "Dua Lulu Wula, Ngae Longgo Leja and Ata Mata Wena Tana".